2015
DOI: 10.1038/pr.2015.74
|View full text |Cite
|
Sign up to set email alerts
|

Why do children decide not to participate in clinical research: a quantitative and qualitative study

Abstract: Background: More pediatric drug trials are needed, but although specific pediatric regulations warrant safety, recruitment of children for these trials remains one of the main difficulties. Therefore, we investigated potential determining factors of nonparticipation in clinical research, in order to optimize research participation of children by recommending improved recruitment strategies. Methods: Between 1 January 2012 and 1 January 2014, we performed a prospective study among161 pediatric patients, aged 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Multiple patients and caregivers identified altruism as a major reason they participated in research. These findings are consistent with a study done by Hein et al which reported that children’s decisions to participate in research were positively influenced by the prospect of helping others [15]. Another reason that patients and caregivers cited participating in research was to expand their own knowledge.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Multiple patients and caregivers identified altruism as a major reason they participated in research. These findings are consistent with a study done by Hein et al which reported that children’s decisions to participate in research were positively influenced by the prospect of helping others [15]. Another reason that patients and caregivers cited participating in research was to expand their own knowledge.…”
Section: Discussionsupporting
confidence: 91%
“…Time commitment and invasiveness of the study were found to be key hindrances to recruitment. Time constraints and direct burden have previously been shown to discourage pediatric research participation when participants are above the age of 9 years [15]. In our interviews, participants also indicated they were less inclined to join drug studies.…”
Section: Discussionmentioning
confidence: 73%
“…Some institutions have advisory boards of child and adolescent participants who can share perspectives about which experiences are burdensome in research [61]. Advisory groups like these can help to raise awareness about what expectations are reasonable for child research participants.…”
Section: Considerations For Research Practicesmentioning
confidence: 99%
“…Advisory groups like these can help to raise awareness about what expectations are reasonable for child research participants. One consideration to make research design more flexible is to consider modifying follow up conversations about study progress through digital outlets, such as phone calls or online platforms [61]. By listening to children’s perspectives on hindrances to participating in research, providers may be able to alter their study designs in ways that accommodate the child’s needs, thus improving adherence to studies overall [20].…”
Section: Considerations For Research Practicesmentioning
confidence: 99%
“…In this issue, Hein et al (1) make an important contribution to our understanding of why children may not participate in research. Previously, Hein et al reported that almost 40% of children aged between 6 and 17 y were judged incompetent to give consent, with age a key determining factor (2).…”
mentioning
confidence: 99%